Added mechanical and physiological loads during swimming with a drag suit - Taguchi, N.; Shibayama, H.; Miyashita, M. (Swimming Science V, 1988)
While swimming at a constant velocity, the swimmer must exert a propulsive force to overcome water resistance. Therefore, numerous studies have reported on water resistance in the static position in relation to velocity, body size, and so forth (Alley, 1952; Oarys, Jiskoot, Risken, & Brouwer, 1974; Karpovich & Millman, 1944; Miyashita & Tsunoda, 1978). Competitive swimming has developed rapidly, partly because of the marked increase in the volume of training (Holmer, 1979). In addition, various devices for training may have contributed to the development of world records. Recently, a swimming training device called a drag suit has been developed to increase drag force. The purpose of the present study was to investigate the differences in water resistance and physiological responses such as heart rate (HR) and blood lactate (La) while wearing a drag suit and a normal suit. This study was pretested on December 23, 1985, and the actual testing was performed from December 24 to 26, 1985.